DECISION SUPPORT SYSTEM FOR ADMISSION OF SINGLE TUITION MONEY SCHOLARSHIP AT VICTORY UNIVERSITY SORONG USING THE WEIGHTED PRODUCT METHOD - Melda Agnes Manuhutu (Electro Luceat, 2021)
The Indonesian state is very aware of the importance of education and supports every citizen to achieve a proper education. This is written in the 1945 Constitution article 31 paragraph 1. Indonesia through the government has shown its support through various programs provided to ensure that every citizen from all walks of life can access education. One of the government programs that is very useful is the UKT scholarship. UKT can be used by all universities in Indonesia, one of which is Victory Sorong University which is one of the private universities in West Papua Province. In conducting the selection of the scholarship, the university, in this case the University of Victory Sorong, has been computerized but is still experiencing difficulties due to the large number of prospective scholarship recipients. The Student Affairs Bureau as the data manager for prospective UKT student recipients still uses the system manually from the past until now using Microsoft Excel and has experienced problems other than because of the large number of prospective students who register for the selection of scholarship recipients also because the selection process takes quite a lot of time. So it is necessary to implement a Decision Support System for receiving single tuition scholarships at Victory Sorong University using the Weighted Product Method so that the SPK System is designed to be able to help speed up and facilitate the granting of scholarships in making accurate decisions for students who are eligible to receive scholarships or not.